Google Earth Media-Assisted Contextual Learning Strategies in Improving Social Studies Learning Outcomes of Junior High School Students - Shasliani Shasliani; Ilma Indriasri Pratiwi (UIN Fatmawati Sukarno Bengkulu, 2026)
This study aims to determine the effectiveness of using Google Earth in a contextual learning strategy on students' social studies learning outcomes. The problem in this study is the low learning outcomes of students in social studies due to the lack of use of interactive learning media and learning strategies that do not connect the material to real-life contexts. Therefore, learning innovations are needed to improve student understanding and learning outcomes. This study used a quantitative approach with a One Group Pretest-Posttest design. The subjects were ninth-grade students totaling 30 students. Data collection was conducted through learning outcome tests administered before (pretest) and after (posttest) the treatment. Data were analyzed using descriptive and inferential statistics, namely paired sample t-tests to determine differences in learning outcomes before and after the treatment. The results showed an increase in student learning outcomes after implementing the contextual learning strategy with Google Earth. This was demonstrated by a higher average posttest score compared to the pretest, as well as the results of the hypothesis test, which showed a significant difference. Therefore, it can be concluded that using Google Earth in a contextual learning strategy is effective in improving students' social studies learning outcomes.